Development of low-cost LED-driven boxing machine - Muhammad Muhaimim, Mahmud; Muhammad Haniff, Gusrial; Nur Aqilah, Othman; Mohd Hasnun Ariff, Hassan (Springer, Singapore, 2026)
This project aims to examine the usage of different sensors in the development of a cost-friendly boxing workout machine with the incorporation of light-emitting diodes (LEDs) sequence for indication purposes. This development is an alternative to the usage of a traditional monotonous punching bag by boxing athletes for training purposes where unattractive and not interactive traditional style makes the athletes felt less motivation. Lack of real-time feedback also affects the athlete’s performances. Suitable sensors to be incorporated are selected based on several criteria such as sensitivity and precision, durability, practical–ity and costing. LED strip and LED ring using LED sequence approach will be included in the design which function as a real-time feedback that controlled by push buttons to indicates different reaction time by varying the LED strip speed as well as its ON and OFF states. The system’s testing results indicated that the proposed sensor is suitable and practical for the boxing training purposes in real applications.